Anthocyanins and Anthocyanin-Derived Products in Yeast-Fermented Beverages - Lavinia Liliana Ruta; Ileana Cornelia Farcasanu (Antioxidants, 2019)
The beverages obtained by yeast fermentation from anthocyanin-rich natural sources (grapes, berries, brown rice, etc.) retain part of the initial pigments in the maturated drink. During the fermentation and aging processes anthocyanins undergo various chemical transformations, which include reactions with glycolytic products (especially pyruvate and acetaldehyde) or with other compounds present in the complex fermentation milieu (such as vinylphenols obtained from cinnamic acids by means of a yeast decarboxylase) yielding pigments which can be more stable than the initial anthocyanins. Overall, these compounds contribute to the organoleptic traits of the mature product, but also to the overall chemical composition which make the yeast fermented beverages important sources of dietary antioxidants. In this review, we focused on the studies regarding the changes underwent by anthocyanins during yeast-mediated fermentation, on the approaches taken to enrich the fermented beverages in anthocyanins and their derived products, and on the interrelations between yeast and anthocyanin which were of relevance for obtaining a high-quality product containing optimum amounts of anthocyanin and anthocyanin-derived products.